1974
DOI: 10.1103/physrevb.10.2457
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of theCd3As2-

Abstract: The near-normal-incidence, room-temperature reflectance spectra of the Cd, As, -Cd,P, semiconductor alloy system have been measured for photon energies 0.083 & F. & 21 eV. Synchrotron radiation has been used to extend the measurements to 30 eV for Cd, As, . These spectra are similar to those of III-V compounds. Comparison of the primary, reflectance data with the results of others and with the band-structure calculations has been made, The reflectance has been analyzed via the Kramers-Kronig relations. %'e rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…All these data sets, as well as the data of Ref. [24], show rather similar overall reflectivity with two strong peaks at approximately 1.8 and 4 eV; the peak at 1.8 eV shows up in our data as well. We have found that at frequencies below 1.2 eV (10 000 cm −1 ) all these different extrapolations affect the outcome of the Kramers-Kronig analysis only marginally.…”
Section: Kramers-kronig Analysissupporting
confidence: 85%
See 2 more Smart Citations
“…All these data sets, as well as the data of Ref. [24], show rather similar overall reflectivity with two strong peaks at approximately 1.8 and 4 eV; the peak at 1.8 eV shows up in our data as well. We have found that at frequencies below 1.2 eV (10 000 cm −1 ) all these different extrapolations affect the outcome of the Kramers-Kronig analysis only marginally.…”
Section: Kramers-kronig Analysissupporting
confidence: 85%
“…[24] by three other data sets available in the literature for the frequency range from approximately 1 to 5 eV. Namely, we used: (i) the polycrystalline data from Ref.…”
Section: Kramers-kronig Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, let us consider Cd 3 As 2 : the experimental values 24-26 of the Fermi velocity are typically in the range 10 5 − 10 6 m/s, while the dielectric constant has been measured to be κ ∼ 20 − 40, 67,68 suggesting coupling values in the range α ∼ 0.1 − 1. Equation (208) then suggests that our second-order perturbative analysis is likely to be valid for coupling values toward the lower end of this range, but as α approaches unity, the results become questionable.…”
Section: Beta Functions and Rg Equationsmentioning
confidence: 99%
“…This would seem to imply that perturbation theory is reliable over a much wider range of values of α in the 3D case relative to the 2D case. In particular, with experimental values of α ∼ 0.1-1 in typical 3D Dirac materials (e.g., in Cd 3 As 2 , dielectric constants in the range κ ∼ 20-40 have been measured 67,68 , while velocities are typically [24][25][26] in the range 10 5 -10 6 m/s), we might expect perturbation theory to give quantitatively reliable results since the condition α ≪ α c applies here. However, we see from the equation for the velocity renormalization that the second-order correction has again the opposite sign relative to the first-order result, producing a second special value of α, α * = 3π/N , where the second-order term is equal in magnitude to the leading-order term.…”
Section: Introductionmentioning
confidence: 99%